Strategi Pengelolaan Lanskap Berkelanjutan di Danau Lido Cigombong, Bogor - Muhammad Haekal Syawie; Hadi Susilo Arifin; Yuli Suharnoto (http://arl.faperta.ipb.ac.id/, 2023)
The utilization of Lido Lake will continue to grow, particularly in the tourism aspect, strenghtened by the 2016-2036 Bogor Regency Spatial Planning (RTRW) and the Government Regulation No. 69 of 2021 which have stipulated it to be a tourism area and a special economic tourism area, respectively. However, at the same time increased garbage accumulation at its lakeside, wastes entering the waters and sedimentation have become prominent problems. This study aimed to develop a management strategy so that the sustainability of Lido Lake can be maintained facing development changes. The SWOT method was used to identify and to analyze the existing internal and external factors in Lido lake including lake's biophysical conditions and preferences/participation of people around the lake. The evaluation of the internal and external factors placed Lido lake in quadrant V forming a strategy to sustain and to maintain. The SWOT matrix recommend 6 management strategies i.e. (1) developing ecotourism as the basis for tourism, (2) implementing and managing environmentally friendly cage fish farming systems, (3) controlling sedimentation in lake waters, (4) Making building design directions on the lakeside, (5) managing the causes of degradation in lake water catchment areas, (6) providing facilities and infrastructure for waste control.